PENERAPAN TEORI PERKEMBANGAN KOGNITIF OLEH JEAN PIAGET TERHADAP KEMAMPUAN MEMECAHKAN MASALAH SISWA SD/MI - Novita, Wantri; Safitri, Aisyah; Dwi saputra, Agra; Lutfhia Ananda, Masykuria; Ersyliasari, Aulia; Rosyada, Amrina (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Piaget's theory of cognitive development seeks to explain how children can adapt and interpret objects and events around them. A problem is a situation faced by people who are aware of the problem and are looking for ways or actions to solve the problem at hand. Problems can arise in many ways, including in learning. Problems can be experienced by anyone, not only adults, children can also experience problems. Problem solving skills are the most important thing in the learning process, with problem solving skills can help students' daily lives. The purpose of this study is to analyze the theory of cognitive development by Jean Piaget on the problem-solving ability of elementary / MI students. The sources of data used in this study are books, journals, articles, and other scientific works. The data collection technique is Literature Study. The results of this study show that the application of Piaget's theory of cognitive development can contribute to the problem-solving ability of elementary / MI students. Different stages of cognitive development affect students' ability to solve problems in different ways. Students who are at higher stages of cognitive development tend to have better problem-solving skills, including analytical skills, systematic problem-solving and flexibility of thinking.